A comparison of Adomian decomposition method and RK4 algorithm on Volterra integro differential equations of 2nd kind - M.C, Kekana; M.Y, Shatalov; S.P, Moshokoa (International Journal of Applied Mathematical Research, 2015)
In this paper, Volterra Integro differential equations are solved using the Adomian decomposition method. The solutions are obtained in form of infinite series and compared to Runge-Kutta4 algorithm. The technique is described and illustrated with examples; numerical results are also presented graphically. The software used in this study is mathematica10.